Uncovering interactions between mycobacterial respiratory complexes to target drug-resistant Mycobacterium tuberculosis - McNeil, Matthew B.; Cheung, Chen-Yi; Waller, Natalie J. E.; Adolph, Cara; Chapman, Cassandra L.; Seeto, Noon E. J.; Jowsey, William; Li, Zhengqiu; Hameed, H. M. Adnan; Zhang, Tianyu; Cook, Gregory M. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium tuberculosis remains a leading cause of infectious disease morbidity and mortality for which new drug combination therapies are needed. Mycobacterial bioenergetics has emerged as a promising space for the development of novel therapeutics. Further to this, unique combinations of respiratory inhibitors have been shown to have synergistic or synthetic lethal interactions, suggesting that combinations of bioenergetic inhibitors could drastically shorten treatment times. Realising the full potential of this unique target space requires an understanding of which combinations of respiratory complexes, when inhibited, have the strongest interactions and potential in a clinical setting. In this review, we discuss (i) chemical-interaction, (ii) genetic-interaction and (iii) chemical-genetic interaction studies to explore the consequences of inhibiting multiple mycobacterial respiratory components. We provide potential mechanisms to describe the basis for the strongest interactions. Finally, whilst we place an emphasis on interactions that occur with existing bioenergetic inhibitors, by highlighting interactions that occur with alternative respiratory components we envision that this information will provide a rational to further explore alternative proteins as potential drug targets and as part of unique drug combinations.